FRI0525 Poly(ADP-RIBOSE) Polymerase-1 (PARP-1) Suppresses the Profibrotic Effects of Transforming Growth Factor-β in Systemic Sclerosis. (10th June 2014) - Zhang, Y.; Palumbo-Zerr, K.; Beyer, C.; Zerr, P.; Liang, R.; Dees, C.; Distler, O.; Schett, G.; Distler, J.H.W.
Abstract : Background: The enzyme poly(ADP-ribose) polymerase-1 (PARP-1) transfers negatively charged ADP-ribose units from the donor β-NAD onto various substrate proteins either as mono- or oligomeric moieties or as linear or branched poly(ADP-ribose) (PAR) chains. Those modifications can have pronounced regulatory effects on the half-life or the enzymatic activity of target proteins. Recent studies demonstrated that PARP-1 can poly(ADP-ribosyl)ates (PARylates) members of the Smad family of transcription factors. However, the role of PARP1 in the pathogenesis of SSc has not been investigated. Objectives: The aim of the study was to characterize the effects of PARP1 on TGFβ signaling and to evaluate its role in the pathologic activation of fibroblasts in SSc. Methods: The expression of PARP1 in human skin and in experimental fibrosis was determined by qPCR and immunohistochemistry. TGFβ signalling was analysed by Smad reporter assays and target gene analysis after 1mM selective PARP1 inhibitor 3-Aminobenzamide (3AB). Bleomycin-induced skin fibrosis and Tsk-1 mice were used to evaluate the effect of PARP inhibition (10mg/kg/d 3AB) in vivo . Results: Decreased expression of PARP1 was detected by immunohistochemistry in skin sections of SSc patients, particularly in fibroblasts. Inhibition of PARylation by 3AB augmented the stimulatory effects of TGFβ on fibroblasts in vitro . PARP1 inhibition increased Smad dependent transcription in reporter assays and promoted the transcription of TGFβ/Smad target genes. Treatment with 3AB also stimulated the collagen release and fostered the expression of contractile proteins with increased expression of α-smooth muscle actin (α-SMA) and enhanced formation of stress fiber formation compared to fibroblasts stimulated with TGFβ alone. Inhibition of PARylation also exacerbated experimental fibrosis in vivo . Treatment with 3AB induced a more severe fibrotic response to bleomycin with increased dermal thickening by up to 103% (p<0.0001), hydroxyproline contents and myofibroblast counts compared to control mice (p<0.0001 and p=0.0059). Inhibition of PARylation also strongly exacerbated fibrosis in Tsk-1 mice. Meanwhile, after bleomycin-injection, dermal thickening, hydroxyproline contents and myofibroblast counts of PARP1 knockout mice are increased by 85% (p=0.0046), 67% (p=0.0098) and 56% (p=0.0043) compared to wild-type mice. Conclusions: We demonstrate that PARP1 negative regulates canonical TGFβ signalling. The down-regulation of PARP1 in SSc fibroblasts may thus directly contribute to hyperactive TGFβ signalling and to persistent fibroblast activation in SSc. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2771